Senescence-Induced Atherosclerosis: The Potency of Senolytic Therapy - Ratih, Udani Sari; Iswanti, Febriana Catur (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
The aging process is an inevitable occurrence that involves physiological changes at the cellular level. The presence of intrinsic and extrinsic stressors can cause cellular damage, leading to senescence and premature aging. Senescent cells undergo activation of the p53/p21 and p16INK4a pathways, induce cell cycle arrest, increased expression of senescence-associated beta-galactosidase (SA-β-Gal), and secretion of SASP (senescence-associated secretory phenotype), leading to "inflamm-aging" or chronic inflammation associated with senescence. These premature aging and “inflamm-aging” accelerates the occurrence of age-related diseases, one of which is atherosclerosis. The relationship between premature aging, senescence, and atherosclerosis has been a focus of research on pathogenesis, prevention, and therapy. Recent research has emphasized the crucial role of senolytics, compounds or agents capable of eliminating senescent cells, in inhibiting the progression of atherosclerosis and slowing down premature aging. Obtaining a more comprehensive understanding of the processes and effectiveness of senolytics in premature aging and atherosclerosis should facilitate the development of more potent medicines to mitigate side effects in the management of cardiovascular disease and extend longevity.